Avaliação e persuasão em abstracts de artigos de pesquisa experimental em medicina - Spinelli, Maria Dulce Patané (2005)
The present study aimed at investigating the use of evaluative resources in experimental research article abstracts in medicine, and how these resources help the writers persuade their readers of the truthfulness and validity of their research. The study was based mainly on the Systemic-Functional Grammar (Halliday, 1994), according to which language is a semiotic system, where each linguistic choice has meaning and reflects the speaker s social activities. Within this framework, the study follows the concept of evaluation proposed by Thompson and Hunston (2000), to whom this linguistic phenomenon comprehends both modality and attitudinal language. More specifically, I based my analysis on Hunston s model of evaluation in scientific writing (1993, 1994). Finally, I sought support for my analysis in the hedging theory, particularly in the ideas of Salager-Meyer (1994) and Hyland (1996). Besides the linguistic theories highlighted above, this study was guided by the ideas of Latour (1987) and Bazerman (2000) about persuasion in science. The corpus of the study consisted of 50 research article abstracts in medicine, written in Portuguese and published in the SciELO online database of scientific journals. The results of the analysis seem to confirm Hunston s (1993, 1994) theory, according to which in scientific texts evaluation is expressed through the objective linguistic elements, and also Latour s (1987) and Bazerman s (2000) assertions that, in science, persuasion is obtained through evidence that proves the accuracy and reliability of the researched reported. Besides, an apparent paradox revealed by the analysis of implicit evaluation in the abstracts points towards a possible transition, in medical research reports, from a positivist paradigm to another, more qualitative and humanistic one